SISTEM PENGAMAN RUMAH BERBASIS SENSOR PIR, CAMERA JPEG, MEMORI SD, DAN SMS YANG TAHAN PEMADAMAN LISTRIK - Sari, Susanti Mayang; Wahyuni, Lutfiah Tri; Andyana, Diandra Rizky (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Based on kapolda metrojayaâs data, recorded many cases of theft house in Jakarta in 2012 amounted to 113 cases, while in 2013 there are 60 cases of theft. (Tribunnews.com, Jakarta, 2013). Increasing the crime rate in Indonesia. Make a security very important. Thus we need home security technology system to felt save. So the author want to develop a home security system that is efficient, convenient, and can keep running even when the power goes out. This activity is done by theoretical studies, based on existing theories and make modifications based on the results. At the end of the activities of a team of writers will produce a prototype system based home security PIR sensor, camera JPEG, SD memory and SMS are resistant to power outages which can run well. The products of this technology is expected to produce a new breakthrough for the security system in Indonesia.